2013
DOI: 10.1002/jmv.23626
|View full text |Cite
|
Sign up to set email alerts
|

New proposal for response‐guided peg‐interferon‐plus‐ribavirin combination therapy for chronic hepatitis C virus genotype 2 infection

Abstract: This study aimed to determine the most suitable duration of pegylated-interferon (Peg-IFN)-plus-ribavirin combination therapy in patients infected with hepatitis C virus (HCV) genotype 2 who had not achieved rapid virological response (serum HCV RNA disappearance after 4 weeks of therapy). HCV genotype 2 patients (n = 182) with a high viral load received >80% of the standard Peg-IFN-plus-ribavirin dose for at least 24 weeks, and their final virological responses were studied. Patients were classified into "rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In this study, we demonstrated that 48-week treatment with Peg-IFN plus weight-based RBV provided a greater SVR rate than 24-week treatment (70.2% versus 46.2%) in treatment-naïve HCV-2 patients not achieving RVR. Our results were in line with previous reports from U.S. and Japan showing that the beneficial effects of extending the treatment duration to 36–48 weeks for these patients 21 22 . In the N-CORE study, Shiffman et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we demonstrated that 48-week treatment with Peg-IFN plus weight-based RBV provided a greater SVR rate than 24-week treatment (70.2% versus 46.2%) in treatment-naïve HCV-2 patients not achieving RVR. Our results were in line with previous reports from U.S. and Japan showing that the beneficial effects of extending the treatment duration to 36–48 weeks for these patients 21 22 . In the N-CORE study, Shiffman et al .…”
Section: Discussionsupporting
confidence: 93%
“…In patients with HCV-2 infection, those achieving rapid virologic response (RVR) have comparable SVR rates by a truncated (12–16 weeks) or standard (24 weeks) duration of Peg-IFN plus RBV therapy 12 18 19 . However, in HCV-2 patients not achieving RVR, the benefits of improving the SVR rates by extending the treatment duration from 24 weeks to 36–48 weeks or by using weight-based (1,000–1,200 mg/day) rather than flat (800 mg/day) RBV dosages are controversial 20 21 22 23 . Although the SVR rates in HCV-2 patients achieving RVR by Peg-IFN plus RBV are similar regardless of interleukin-28B (IL-28B) genotypes, the role of IL-28B genotypes in HCV-2 not achieving RVR has not been fully elucidated 23 24 25 26 .…”
mentioning
confidence: 99%
“…High Mir-122 level, less favorable IL-28 (CT or TT) polymorphism and African-American race are the main host factor leading to poorer SVR [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Subtype 1b is prevalent worldwide [3], while the other genotypes are typically confined to regional epidemics. In brief, subtype 1a is most commonly seen in the USA [4]; subtype 2a and 2b are predominant in North America, Europe and Japan [57]; HCV-3 (predominantly 3a) is the most prevalent genotype in India and Pakistan [8, 9]; genotype 4 is often found in the Middle East and Africa [3]; subtype 5a accounts for at least 50 % of the infections in South Africa [10] and genotype 6 (HCV-6) is frequently seen in southern China and Southeast Asia [1113]. Furthermore, the genotype reportedly confers a different individual response to the commonly used combination therapy interferon (IFN) + ribavirin (RBV).…”
Section: Introductionmentioning
confidence: 99%